2019
DOI: 10.1038/s41418-019-0442-2
|View full text |Cite|
|
Sign up to set email alerts
|

Impaired cellular bioenergetics caused by GBA1 depletion sensitizes neurons to calcium overload

Abstract: Heterozygous mutations of the lysosomal enzyme glucocerebrosidase (GBA1) represent the major genetic risk for Parkinson's disease (PD), while homozygous GBA1 mutations cause Gaucher disease, a lysosomal storage disorder, which may involve severe neurodegeneration. We have previously demonstrated impaired autophagy and proteasomal degradation pathways and mitochondrial dysfunction in neurons from GBA1 knockout (gba1 −/− ) mice. We now show that stimulation with physiological glutamate concentrations causes path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 60 publications
0
25
0
Order By: Relevance
“…A global pseudohypoxia, of course, would be also expected to be a proximate cause of neurological dysfunction (since neurons are highly ATP-dependent cells, highly susceptible to disturbances in cellular bioenergetic processes) (Hoyer 1990 ; Zeiger et al 2011 ; Funes et al 2014 ; Nicholls et al 2015 ; Hebert-Chatelain et al 2016 ; Plotegher et al 2020 ). We hypothesize that neuronal pseudohypoxia may also potentially contribute to the process of delayed neurodegeneration (Alzheimer-like symptoms) in DS.…”
Section: Implications Conclusion and Outlookmentioning
confidence: 99%
“…A global pseudohypoxia, of course, would be also expected to be a proximate cause of neurological dysfunction (since neurons are highly ATP-dependent cells, highly susceptible to disturbances in cellular bioenergetic processes) (Hoyer 1990 ; Zeiger et al 2011 ; Funes et al 2014 ; Nicholls et al 2015 ; Hebert-Chatelain et al 2016 ; Plotegher et al 2020 ). We hypothesize that neuronal pseudohypoxia may also potentially contribute to the process of delayed neurodegeneration (Alzheimer-like symptoms) in DS.…”
Section: Implications Conclusion and Outlookmentioning
confidence: 99%
“…We show in the present study that these glucosylceramides are increased in the DRGs of Pink1SNCA mice strengthening the idea that they contribute to the pathology of sensory neurons. Mutations of GBA1, the key lysosomal enzyme catalyzing GlcCer degradation, have been associated with autophagolysosmal dysfunctions [66,67], increased alpha-synuclein toxicity [27,68] and disruptions of mitochondrial energy production [49]. GBA1 expression was unaltered in the DRGs of Pink1SNCA mice, and the ultrastructural morphology of lysosomes and lipid droplets in DRG neurons appeared to be normal for the age.…”
Section: Discussionmentioning
confidence: 99%
“…So far, most studies addressing the functional consequences of GBA1 deletion assumed that the observed pathology was caused by glucosylceramides without directly measuring these lipids. GBA1 deletion or mutation increased alpha-synuclein aggregates [26,27], led to mitochondrial calcium overload [49], ER stress [69] and disruption of autophagolysosomal pathways [67].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A growing number of studies have found that the Glu is closely associated with the etiology and pathology of many neurological and psychiatric disorders, such as cerebral ischemia, epilepsy, Alzheimer's disease, Huntington's disease, schizophrenia, and Pico disease [14]. Oxidative stress caused by Glu is an important cause of neurodegenerative diseases [15,16], high concentration of Glu inhibits cysteine/glutamate antiporter or system x-CT in neuronal cells, causes calcium overload that interferes with mitochondrial respiratory chain function, thereby inhibiting cystine uptake and causing intracellular glutathione (GSH) deprivation and ROS accumulation, and ultimately leading to cell necrosis or apoptosis [17,18]. Moreover, studies have shown that the caspase-dependent apoptotic pathway is related with Glu-neurotoxicity [19].…”
Section: Introductionmentioning
confidence: 99%